Pepsinogen testing for evaluation of the success of Helicobacter pylori eradication at 4 weeks after completion of therapy - Marcis Leja; Sanita Lapina; Inese Polaka; Dace Rudzite; Ilona Vilkoite; Ilva Daugule; Anna Belkovets; Sergey Pimanov; Jelena Makarenko; Ivars Tolmanis; Aivars Lejnieks; Viesturs Boka; et al. (Medicina, 2014)
Background and objective: Pepsinogen levels in plasma are increased by inflammation in the gastric mucosa, including inflammation resulting from Helicobacter pylori infection. A decrease in pepsinogen II level has been suggested as a reliable marker to confirm the successful eradication of infection. The aim of our study was to evaluate the potential role of pepsinogens I and II, gastrin-17 and H. pylori antibodies in confirming successful eradication. Material and methods: Altogether 42 patients (25 women, 17 men), mean age 45 years (range 23–74), were enrolled. Pepsinogens I and II, gastrin-17 and H. pylori IgG antibodies were measured in plasma samples using an ELISA test (Biohit, Oyj., Finland) before the eradication and 4 weeks after completing the treatment. The success of eradication was determined by a urea breath test. Results: Eradication was successful in 31 patients (74%) and unsuccessful in 11 patients (26%). Pepsinogen II decreased significantly in both the successful (P = 0.029) and unsuccessful (P = 0.042) eradication groups. Pepsinogen I decreased significantly in the successful (P = 0.025) but not the unsuccessful (P = 0.29) eradication group. The pepsinogen I/II ratio increased in the successful eradication group (P = 0.0018) but not in the group in which treatment failed (P = 0.12). There were no differences in gastrin-17 or H. pylori antibody values. Conclusions: A decrease in pepsinogen II levels cannot be used as a reliable marker for the successful eradication of H. pylori 4 weeks after the completion of treatment. The increase in pepsinogen I/II ratio reflects differences in pepsinogen production following the eradication irrespective of improvement in atrophy.